Measurements and micro-mechanical modelling of the response of sintered titanium foams - Siegkas, Petros; Petrinic, N.; Tagarielli, V. L. (My University, 2016)
Titanium foams of relative density in the range 0.35-0.50 are tested in quasi-static compression, tension and shear. The response is ductile in compression but brittle, and weaker, in shear and tension. Virtual foam microstructures are generated by an algorithm based on Voronoi tessellation of three-dimensional space, capable of reproducing the measured size distribution of the pores in the foam. Finite Element (FE) simulations are conducted to explore the mechanical response of the material, by analysing the elasto-plastic response of a statistical volume element (SVE). The simulations correctly predict the ductile compressive response and its dependence on relative density.
Keywords: Titanium; Compression; FEM; Foam; Shear; Tension; Voronoi